Chemical and Sensory Profiles of Sauvignon Blanc Wine Following Protein Stabilization Using a Combined Ultrafiltration/Heat/Protease Treatment - Sui, Yihe; Wollan, David; McRae, Jacqui M.; Muhlack, Richard; Capone, Dimitra L.; Godden, Peter; Wilkinson, Kerry L. (Frontiers in Nutrition, 2022)
Ultrafiltration (UF) was evaluated as a process by which proteins can be selectively removed from white wine as an alternative approach to protein stabilization than traditional bentonite fining. Unfined Sauvignon Blanc wine (50 L) was fractionated by UF and the retentate stabilized either by heat and/or protease treatment or bentonite fining before being recombined with the permeate. The heat stability of recombined wine was significantly improved when retentate was heated following protease (Aspergillopepsin) addition and subsequently stabilized by bentonite treatment. The combined UF/heat/protease treatment removed 59% of protein and reduced the quantity of bentonite needed to achieve protein stability by 72%, relative to bentonite treatment alone. This innovative approach to protein stabilization had no significant impact on wine quality or sensory characteristics, affording industry greater confidence in adopting this technology as a novel approach to achieving protein stability.